FDI, Technology, and Upgrading: Rethinking Innovation Policy in Latin America - Moya, Franklin; Pinzón, Katherin (Papeles de Europa, 2025)
The relationship between foreign direct investment (FDI), digitalization and global value chains (GVCs) has traditionally been understood as an interdependent process. This paper proposes a development pathway for Latin America based on FDI that enables knowledge transfer and strengthens local technological capabilities, aiming to overcome dependency dynamics. This approach may foster a more productive integration into GVCs by leveraging the window of opportunity created by new digital technologies. The paper also explores key elements for innovation policy, emphasizing access to and use of digital technologies as critical factors for productivity and upgrading.
Keywords: Foreign Direct Investment (FDI); Global Value Chains (GVC); Digitalization and Technological change